An Approach for Designing and Exploring Customizable Narrative Data Visualizations - Correa, Claiton Marques; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Narrative data visualizations are proposed to present data in a story-like form that may improve its understanding. Besides this, the end-users of visualizations may have varying needs and preferences in how data is presented or organized, which makes end-user development a promising topic to be blended into narrative data visualization research. This paper presents a doctoral research journey to define an approach to assist visualization designers in planning narrative data visualizations with customization features called customizable narrative data visualizations. We defined a four-stage methodology to cope with our research goals, ranging from understanding the problem to applying the solution. Throughout our research, we conducted different studies, including systematic reviews and user studies like focus groups and workshops, to outline and analyze our process. The process was considered useful and promising in assisting designers in identifying narrative elements from data and defining how the end-users can customize a narrative visualization. Besides the process itself, the studies presented valuable contributions to the HCI area, such as grasping the perspectives of designers and end-users regarding customizable narrative visualizations. We believe our results are important findings that help set the path for researchers and professionals interested in creating narrative data visualizations in which end-users have agency over the content displayed.